Business organizational forms - Li, Wei; Maslak, M. V.; Pererva, P. G. (Національний технічний університет "Харківський політехнічний інститут", 2024)
Choosing the appropriate organizational form depends on many factors, including the level of risk, taxation, ownership structure and the desirability of business expansion. We offer the following forms of business organization for use. The choice of the optimal organizational form of business should be carried out taking into account the specifics of the activity, development strategy, risks and legal aspects. To determine the best option, it is recommended that you consult with professional lawyers or business consultants.
Організаційні форми бізнесу
Keywords: risk; taxation; production organization; business; factors; efficiency